The impact of board and ownership on the value of firms listed on FTSE Bursa Malaysia EMAS Shariah index / Adnan Ameen Abdullah Bakather - Abdullah Bakather, Adnan Ameen (Institute of Graduate Studies, UiTM, 2013)
The flourishing of the Islamic financial industry has been widely recognized worldwide. However, the corporate governance of such an industry is still questionable, in particular, the Islamic equity markets. The review of literature showed the corporate governance of Shariah approved firms has only been empirically tested in few studies. These studies have failed to produce consistent evidence on the impact of governance mechanisms on these Shariah approved firms. In addition, these studies ignored the Islamic perspective of corporate governance. The study mainly investigates the relationship between the corporate governance mechanisms and value of firms listed on FTSE Bursa Malaysia EMAS Shariah Index over the period of 2007 to 2009. In addition, the current study examines the moderating effects of corporate social performance and corporate financial performance on the relationship between these mechanisms and firm valuation. Several statistical techniques have been adopted in order to test the study hypotheses. These include the descriptive statistics, univariate tests and the regression analysis. The Ordinary Least Squares (OLS) regression analysis within the framework of the Moderated Multiple Regression (MMR) framework has been used to test the hypotheses…